O presente de Joel Rufino dos Santos: reflexões sobre o negro e as relações raciais - Carvalho, Andressa Monteiro de (2019)
This dissertation aims to discuss a book entitled "The Gift of Ossanha" (2006) by Joel Rufino dos Santos, as a narrative that assists the understanding about black people in school. Taking a infant story book as the main object of analysis, we intend to reflect on the racial relations in society and, especially in the school context. The Primary was a discussion about the life and work of the author, Joel Rufino, having developed the long journeys of his academic, political and personal career, the latter being used in the writing of the work here highlighted. Then the ear of the book was worked, more specifically, understanding the messages that the author wanted to convey. In the part of the docing the dissertation, objective, to, to enter in the document of the education, the objective of the practice in educative emancipating.